Suplementasi Kalsium Dan Faktor Risiko Hipertensi Pada Ibu Hamil (Tinjauan Literatur terhadap Intervensi Nutrisi dan Pendekatan Pencegahan) - NIAR NIAR; Nilawati Uly; Andi Alim; Nur Anita; Nur Aisyah (LPPM STIKES Marendeng Majene, 2026)
Hypertensive disorders during pregnancy remain a major cause of maternal and fetal morbidity and mortality worldwide. Nutritional interventions, particularly calcium supplementation, have been widely explored as preventive strategies to reduce the incidence of pregnancy related hypertension and preeclampsia. This review aimed to examine the scientific evidence regarding the effectiveness of calcium supplementation in lowering the risk of hypertension among pregnant women and to identify factors associated with the development of hypertensive disorders during pregnancy. A literature review design was employed by analyzing thirty seven national and international scientific publications issued between 2019 and 2025. Relevant studies were identified through searches of PubMed, ScienceDirect, Google Scholar, and Garuda databases, and the findings were synthesized using descriptive analysis. The review demonstrated that calcium supplementation, either administered alone or in combination with vitamin D, contributed to blood pressure reduction and prevention of preeclampsia. In addition, previous hypertension, obesity, maternal age, psychological stress, exposure to cigarette smoke, and excessive salt intake were identified as important contributing factors. Supportive non pharmacological interventions and continuous antenatal monitoring and education were also found to improve blood pressure management during pregnancy. The integration of nutritional and non pharmacological approaches may provide an effective strategy for preventing hypertensive disorders in pregnancy.